Extraglandular orbital adenoid cystic carcinoma - Sami Elhamid; Bahaa Razem; Faiçal Slimani (Elsevier, 2022)
Adenoid Cystic Carcinoma (ACC) is an uncommon malignancy and it's orbital primary presentation with no glandular involvement is exceedingly rare. However, ACC must be considered in the diagnosis of an orbital tumor, since complications such as intracranial spread and recurrence are often described. We present a case of primary orbital ACC treated with surgical excision and the outcome of a long term follow-up in the light of a litterature review.